Strengthening Qur’anic Memorization through the 3T+1M Method: Evidence from a Flagship Tahfidz Program - Idam Mustofa; Syarifah Syarifah; Nabila Zulfia (FONDATIA, 2026)
The flagship tahfidz program at MI Labs Ri’ayatul Ummah Jakarta implements the 3T+1M method (talaqqi, tikrar, tafahhum, and muraja’ah) in daily Al-Qur’an memorization activities; however, its implementation still faces various dynamics, such as differences in students’ memorization abilities, limited instructional time, and the need to strengthen the consistency of muraja’ah outside the madrasah environment. This study aims to describe the application of the 3T+1M method, analyze its effectiveness and efficiency, and identify the challenges and opportunities within the flagship tahfidz program at MI Labs Ri’ayatul Ummah Jakarta. A qualitative descriptive case study approach was employed, with data collected through observation, in-depth interviews, and documentation involving the head of the madrasah, tahfidz teachers, the program coordinator, and students. Data analysis was conducted using an interactive analysis technique, including data reduction, data display, and conclusion drawing. The findings show that the 3T+1M method is implemented systematically through structured stages integrated into the daily tahfidz routine and has proven effective and efficient in improving the quality of students’ Al-Qur’an memorization, as reflected in accurate recitation, increased fluency, basic understanding of verse meanings, and stable retention of previously memorized passages. Nevertheless, challenges remain in the form of heterogeneous student abilities, limited instructional time, and inconsistent muraja’ah at home. The study concludes that the flagship tahfidz program based on the 3T+1M method has strong potential for sustainable development with the support of competent teachers, a religious learning environment, and active parental involvement, and is expected to serve as a reference for the development of tahfidz learning methods oriented toward process quality and the sustainability of learning outcomes.